2012
DOI: 10.1515/hf.2011.168
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobisation of mechanical pulp fibres with sodium dodecyl sulphate functionalised layered double hydroxide particles

Abstract: Hydrogen peroxide bleached spruce ( Picea abies L.) made of thermo mechanical pulp (BTMP) fi bres were modifi ed with layered double hydroxides (LDH). The LDH particles were precipitated onto the BTMP fi bre surfaces from aqueous solutions of urea and NaOH. The modifi ed BTMP was further functionalised with sodium dodecyl sulphate (SDS) surfactant to produce pulp with hydrophobic character. The contact angle measurement with water on paper showed that the functionalisation with SDS was successful. The apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Layered double hydroxides (LDH) were synthesized in the presence of pulp fibers and behaved slightly different due to their change in properties as the LDH crystal growth occurred on the cellulose surface from its nascent state. , For this, pine pulp was used as a substrate to grow Mg- and Al-containing LDH in an aqueous medium. The growth was initiated by the precipitation of Mg and Al precursor solutions under basic conditions (pH ≥9).…”
Section: In Situ Hybridization Of Cellulose Fibers By Ldh Materialsmentioning
confidence: 99%
“…Layered double hydroxides (LDH) were synthesized in the presence of pulp fibers and behaved slightly different due to their change in properties as the LDH crystal growth occurred on the cellulose surface from its nascent state. , For this, pine pulp was used as a substrate to grow Mg- and Al-containing LDH in an aqueous medium. The growth was initiated by the precipitation of Mg and Al precursor solutions under basic conditions (pH ≥9).…”
Section: In Situ Hybridization Of Cellulose Fibers By Ldh Materialsmentioning
confidence: 99%
“…We have previously shown how the surface chemistry of fibers can be changed with LDH and how these fibers behave in injection molded composite structures [28,29]. In this article, we address the chemical and physical characteristics of pulp fibers considering the changes in cellulose polymer chain length, adsorption capacity, thermal behavior and compliance after the lss, hss and Uhyd synthesis routes, which all involve in situ LDH particle synthesis on fiber surfaces.…”
Section: mentioning
confidence: 99%
“…Because of these flexible properties in terms of chemical compositions, LDHs have been widely studied in literature, particularly with respect to applications in heterogeneous catalysis in taking advantages of their unique tunable basic properties and surface area (Tichit et al, 2006 andDebecker et al, 2009). They also find their use as composite applications, catalyst precursors, adsorbents for environmental remediation, as well as carriers for biological materials (Lange et al, 2013, Wang and Hare, 2012, Lange et al, 2012, Zhao et al, 2010a, b, Williams and Hare, 2006, Yan et al, 2011, Zhao et al, 2009, Zhao et al, 2010a, b, Hu and O'Hare, 2005, Oh et al, 2011, Wang et al, 2011. It has been reported that the layered structure of LDH and the derived oxides possesses semiconductor properties which facilitate the transfer of the photo generated electrons on the surface of photo catalyst, which might provide great potential in many applications (Paušová et al, 2015, Gunjakar et al, 2011, Gomes-Silva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%